Ecotourism Impacts on the Economy, Society and Environment of Thailand - Sangpikul, Aswin (Journal of Reviews on Global Economics, 2017)
During the past decade, there have been a number of ecotourism studies in various disciplines to provide a knowledge foundation for sustainable tourism development. However, most prior studies have examined the contributions of the ecotourism destinations in the economic and/or environmental dimensions. Little research has investigated the contributions of the ecotourism businesses in terms of business practices and their products to the three dimensions of sustainable development. This paper examines how ecotourism tour operators and their guided tours contribute to the development of economic, social and environmental dimensions at ecotourism sites and local communities. Data were collected from ecotourism tour operators through the interview and observation methods, and the contents were analyzed in accordance with ecotourism concepts and principles. The paper reveals that the practices of tour operators and their guided tours contributed economic, social, and environmental benefits to the ecotourism destinations and local communities. Interestingly, this paper finds that the length (duration) and types of guided tours had different contributions and impacts on the three dimensions of sustainability. In particular, guided tours with a local visit contribute greater economic and social benefits to the local areas than tours without a local visit. Recommendations are provided to promote responsible ecotourism business.